2019
DOI: 10.1002/smll.201902926
|View full text |Cite
|
Sign up to set email alerts
|

Tumor pH‐Responsive Albumin/Polyaniline Assemblies for Amplified Photoacoustic Imaging and Augmented Photothermal Therapy

Abstract: Tumor‐microenvironment‐responsive theranostics have great potential for precision diagnosis and effective treatment of cancer. Polyaniline (PANI) is the first reported pH‐responsive organic photothermal agent and is widely used as a theranostic agent. However, tumor pH‐responsive PANI‐based theranostic agents are not explored, mainly because the conversion from the emeraldine base (EB) to emeraldine salt (ES) state of PANI requires pH < 4, which is lower than tumor acidic microenvironment. Herein, a tumor pH‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 51 publications
1
68
0
Order By: Relevance
“…Switching from the EB state to the ES state in the presence of oxidative species or an acidic environment leads to a red shift of PANI’s absorption peak from the visible to the NIR region due to charge transmission between benzenoid and quinoid rings through enhanced electron movement, leading to potential PTT applications [ 14 , 29 ]. Therefore, PANI has been exploited in PTT applications owing to its biocompatibility and high photothermal conversion efficiency [ 14 , 29 , 30 , 31 ]. Unlike organic dyes, PANI exhibits excellent photostability upon light irradiation, thus enabling repeated phototherapeutic treatments [ 28 ].…”
Section: Chemical Structure and Stability Of Panimentioning
confidence: 99%
See 4 more Smart Citations
“…Switching from the EB state to the ES state in the presence of oxidative species or an acidic environment leads to a red shift of PANI’s absorption peak from the visible to the NIR region due to charge transmission between benzenoid and quinoid rings through enhanced electron movement, leading to potential PTT applications [ 14 , 29 ]. Therefore, PANI has been exploited in PTT applications owing to its biocompatibility and high photothermal conversion efficiency [ 14 , 29 , 30 , 31 ]. Unlike organic dyes, PANI exhibits excellent photostability upon light irradiation, thus enabling repeated phototherapeutic treatments [ 28 ].…”
Section: Chemical Structure and Stability Of Panimentioning
confidence: 99%
“…It was reported that pH response range of PANI can be tuned by self-doping of PANI through introduction of acidic groups into the PANI chains [ 73 ] or by improving the charge transfer rate via incorporation of conductive nanomaterials into PANI matrix [ 74 ]. When relying on this strategy, researchers have made attempts to improve the application of PANI as PTA in cancer treatment [ 31 , 50 , 51 , 52 ]. Hong and coworkers synthesized PANI nanoparticles by incorporating lauric acid (LA) as a stabilizer and localized dopant [ 50 ].…”
Section: Pani-based Biomaterials For Tumor Ablationmentioning
confidence: 99%
See 3 more Smart Citations